A thousand and one [videorecording (Blu-Ray)] - Rockwell, A. V.; Taylor, Teyana, 1990-; Cross, Josiah; Catlett, Will, 1982-; Adetola, Aaron Kingsley; Courtney, Aven; Abney, Terri; Reynolds, Delissa; Lenox, Adriane (Universal, 2023)
Follows unapologetic and free-spirited Inez, who kidnaps her six-year-old son, Terry, from the foster care system. Holding onto their secret and each other, mother and son set out to reclaim their sense of home, identity, and stability in a rapidly changing New York City.